EDUKASI TENTANG PANGAN LOKAL SEBAGAI ASUPAN GIZI HARIAN BAGI BALITA UNTUK PENCEGAHAN STUNTING DI DESA SIBEDI, KECAMATAN MARAWOLA, KABUPATEN SIGI - Ummu Aiman; Nurulfuadi Nurulfuadi; Hijra Hijra; Aldiza Intan Randani; Febiani Riskika; Devi Nadila; Dian Novriyanti; Try Nur Ekawati (Universitas Mataram, 2025)
The stunting problem in Sigi Regency remains a public health concern that requires specific interventions, including in Marawola District, Sibedi Village, where the prevalence rate reached 25.6%. This figure is higher than the national stunting prevalence of 15.8%, indicating the need for targeted efforts to reduce it. This community service activity aimed to enhance housewives’ understanding of the causes and risks of stunting among toddlers, introduce the nutritional content of local food sources, and improve their skills in processing nutritious local foods through practical daily recipes for toddlers. The activity was conducted through socialization sessions and the distribution of pocket books containing local food-based recipes as references for preparing daily family meals. The results demonstrated that this program was effective in increasing mothers’ knowledge regarding stunting prevention. Based on pre- and post-test results, the proportion of participants with a high level of knowledge increased from 22.9% to 91.4%. This finding indicates a significant improvement in nutrition literacy, particularly in understanding the definition of stunting, associated risk factors, and the importance of meeting balanced nutritional needs.